The - Wade, Terence Leslie Brian (Oxford University Press, 2002)
Comprehensive and easy to use, with coverage of all the key points of Russian grammar, it is the ideal support book for any Russian language course and is ideal for use with Oxford's Take off in Russian and other audio language learning packs. Thousands of examples in an instantly accessible layout show how the language works. Detailed tables of regular and irregular Russian verbs feature ultra-clear explanations and an easy-access design. Finally, all grammatical terms are explained in a glossary